2010
DOI: 10.1111/j.1740-0929.2010.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary addition of seaweed and licorice on the immune performance of pigs

Abstract: In pig production, dietary additive antibiotics are usually used for growth stimulation and disease prevention, although there is public concern about the increased incidence of resistant antibiotics and food safety. It is possible that such antibiotics might be replaced by naturally derived products such as seaweed and licorice. In this study, we evaluated the effect of dietary addition of seaweed and licorice on enhancing the immune function in swine. The animals of each group (eight animals per group) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 32 publications
0
40
0
1
Order By: Relevance
“…However, the concentration of essential amino acids in seaweeds on a whole biomass basis is considerably lower than traditional sources and is not adequate as a protein component of compound diets for mono-gastric livestock. This does not detract from their positive health benefits to humans (Fleurence et al, 2012;Holdt & Kraan, 2011;Mabeau & Fleurence, 1993) and livestock (at low inclusion levels - Dierick, Ovyn, and De Smet (2009), Katayama et al (2011)), where a low calorific value and high mineral content can be desirable. If seaweed protein is to be used for commercial mono-gastric livestock production it needs to be concentrated by the removal of fibre and ash components, or selectively extracted so that the concentration of essential amino acids can be increased to comparable levels with other protein products.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the concentration of essential amino acids in seaweeds on a whole biomass basis is considerably lower than traditional sources and is not adequate as a protein component of compound diets for mono-gastric livestock. This does not detract from their positive health benefits to humans (Fleurence et al, 2012;Holdt & Kraan, 2011;Mabeau & Fleurence, 1993) and livestock (at low inclusion levels - Dierick, Ovyn, and De Smet (2009), Katayama et al (2011)), where a low calorific value and high mineral content can be desirable. If seaweed protein is to be used for commercial mono-gastric livestock production it needs to be concentrated by the removal of fibre and ash components, or selectively extracted so that the concentration of essential amino acids can be increased to comparable levels with other protein products.…”
Section: Resultsmentioning
confidence: 96%
“…There is little literature on incorporating seaweeds as a protein source into the diets of poultry and swine. In contrast, there are many studies examining the functional effects of seaweed and their extracts on immune function, gut health, and meat and egg quality (Katayama et al, 2011;Kulshreshtha et al, 2014;Michalak et al, 2011;Walsh, Sweeney, O'Shea, Doyle, & O 'Doherty, 2013). However, these studies use low inclusion levels (<5%) that contribute little protein to the diet or, its corollary, that the seaweeds do not displace traditional protein sources in the feed.…”
Section: The Use Of Whole Seaweeds In Mono-gastric Livestock Dietsmentioning
confidence: 88%
“…Functional polysaccharides such as fucans and alginic acid, derivatives produced by seaweeds, are known to exhibit biologically beneficial properties including anticoagulant, anti-inflammatory, antiviral and antitumoral activities (Wijesinghe adn Jeon, 2012), and dietary supplementation with seaweed gives positive effects in broilers (Ventura et al, 1994). Although, however, numerous studies were reported that seaweeds have potential as effective additives, some of seaweed components could interfere with bioavailability of diet (Michel et al, 1996; MacArtain et al, 2007), and availability could be decreased in animals (Katayama et al, 2011). In this regard, research for SF by-products and increased availability by them has not been performed by fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that seaweeds may have an important role in modulating human chronic disease (Brown et al, 2014) or elevating disease resistance by improving immunity in pigs (Maghin, Ratti, & Carino, 2014). Based on this information, we conducted several experiments with seaweeds, especially A. nodosum, as a feed additive, and found that the addition of A. nodosum increased sheep red blood-specific IgG production in serum in pigs (Katayama et al, 2011;Suzuki et al, 2009). Moreover, Dierick, Ovyn, and Smet (2009) reported that A. nodosum addition to pig feed improved the gut health of the weaned piglets.…”
mentioning
confidence: 99%